Mental Health of Pregnant Women during the Covid-19 Pandemic: Scoping Review - Irne Wida Desiyanti; Rosmita Nuzuliana (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
Background: Mental health disorders in pregnant women are highly associated with reduced involvement in support, which can lead to pregnant women having to stay home or be isolated during the COVID-19 epidemic. Here, mental health disorders are including depression, fear, and anxiety. This disorder actually had existed before the pandemic and increased when the WHO announced the COVID-19. Purpose: This study aims to analyze the mental health condition of pregnant women during the COVID-19 pandemic. Methods: In the preparation of this scoping review, three databases are used, namely PubMed, Wiley, and Google Scholar. These databases were used to find the articles. The articles were considered relevant if they could answer some research questions of scoping review by using article search with specific keywords. Some relevant articles were selected by setting inclusion and exclusion criteria. Following that, Prism Flow Chart was used in the selection process to find the right article. Critical Appraisal was then performed to assess the quality of each article. Those articles were further summarized by using Data Charting and compiled for analysis based on the available evidence-based aspect. The last step was reporting the results. Results: In this study, the results obtained were 8 selected articles. A total of 7 articles fall into the grade A category, consisting of 2 articles of non-randomized quantitative research design, 4 descriptive quantitative articles, and 1 qualitative article. 1 article is classified in grade B on descriptive quantitative study design. There are no research articles categorized as grade C. Conclusion: Significantly increased clinical problems related to the mental health of pregnant women during the COVID-19 pandemic are including anxiety, fear, and depressive symptoms. Compared to the pre-pandemic situation, the increase is caused by several factors such as pandemic-related stresses arising from related social restrictions, personal health and the safety of the baby during pregnancy, and the health of family members.